Hydrogen electrolyser technologies and their modelling for sustainable energy production: A comprehensive review and suggestions - Arsad A.Z.; Hannan M.A.; Al-Shetwi A.Q.; Begum R.A.; Hossain M.J.; Ker P.J.; Mahlia T.I. (Elsevier Ltd, 2024)
The advancement of hydrogen technology is driven by factors such as climate change, population growth, and the depletion of fossil fuels. Rather than focusing on the controversy surrounding the environmental friendliness of hydrogen production, the primary goal of the hydrogen economy is to introduce hydrogen as an energy carrier alongside electricity. Water electrolysis is currently gaining popularity because of the rising demand for environmentally friendly hydrogen production. Water electrolysis provides a sustainable, eco-friendly, and high-purity technique to produce hydrogen. Hydrogen and oxygen produced by water electrolysis can be used directly for fuel cells and industrial purposes. The review is urgently needed to provide a comprehensive analysis of the current state of water electrolysis technology and its modelling using renewable energy sources. While individual methods have been well documented, there has not been a thorough investigation of these technologies. With the rising demand for environmentally friendly hydrogen production, the review will provide insights into the challenges and issues with electrolysis techniques, capital cost, water consumption, rare material utilization, electrolysis efficiency, environmental impact, and storage and security implications. The objective is to identify current control methods for efficiency improvement that can reduce costs, ensure demand, increase lifetime, and improve performance in a low-carbon energy system that can contribute to the provision of power, heat, industry, transportation, and energy storage. Issues and challenges with electrolysis techniques, capital cost, water consumption, rare material utilization, electrolysis efficiency, environmental impact, and storage and security implications have been discussed and analysed. The primary objective is to explicitly outline the present state of electrolysis technology and to provide a critical analysis of the modelling research that had been published in recent literatures. The outcome that emerges is one of qualified promise: hydrogen is well-established in particular areas, such as forklifts, and broader applications are imminent. This evaluation will bring more research improvements and a road map to aid in the commercialization of the water electrolyser for hydrogen production. All the insights revealed in this study will hopefully result in enhanced efforts in the direction of the development of advanced hydrogen electrolyser technologies towards clean, sustainable, and green energy. 2023 Hydrogen Energy Publications LLC